ChatGPT and AI in the Universities: An Introduction to the Near Future - A. V. Rezaev; N. D. Tregubova (Moscow Polytechnic University, 2023)
The paper aims to present the theoretical and methodological foundations for developing and implementing artificial intelligence (AI) instruments in higher education within the HumanCentered AI framework and considers ChatGPT as a specific case. It is oriented toward critically analyzing scholarly literature from various disciplines to support a-disciplinary approach to utilizing AI research in higher education. The authors begin by outlining the foundations of the research, then by analyzing the implications of the "lessons" of the COVID-19 pandemic for the development of higher education in the age of AI. This is followed by an analysis of technologies such as ChatGPT that have the potential to radically change higher education in the near future. After that, the authors move on to general remarks about the prospects and challenges of using AI technologies in higher education. The relevance of the research is characterized by the analysis of the latest developments in the field of AI and their possible impact on higher education. The main results of the paper are characteristics of areas in which AI technologies can be implemented in higher education - accreditation and licensing of universities, student recruitment, teaching and learning - as well as areas in which AI technologies should not be used. In conclusion, two hypotheses are formulated, and three general and five specific conclusions about the use of AI technologies in higher education are made.